Media Pembelajaran Pengenalan Sistem Organ Manusia Melalui Augmented Reality Dengan Menggunakan Aplikasi Unity - Murdhani, I Dewa Ayu Sri; Saraswati, I Dewa Ayu Indah; Muhammad, Sholeh (Jurnal SUTASOMA (Science Teknologi Sosial Humaniora), 2023)
In today's modern era, information technology is developing quite rapidly in line with the times. The existence of these developments has had a large and broad impact on the progress of life in all fields. One of the currently developing information technologies is augmented reality (AR). AR can be used in the development of innovation in education. The use of AR can be an effective, fun, and interesting educational medium. The aim of the research is to help students learn more effectively using learning media that combines the real world with digital information through 2D or 3D models. The use of AR is used for the development of biology learning materials. The developed application is expected to make teaching materials easier to understand and students can measure mastery of the material, as well as make it easier to learn in a more active way in a self-paced mode. The research method used is Research and Development (R&D). Using this method can create innovation and improvement in the product/application development process. This research will produce an AR application that explains the discussion of material from human organs, then there is a quiz, and is equipped with 3D objects to provide an interactive learning experience, increase interest in learning, then be able to see and interact with models of human organs virtually. AR-based learning (Education) media was developed using the Unity application.